2012
DOI: 10.1021/ac3020998
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Oxide Nanoparticles as Carriers and Adjuvants for Eliciting Antibodies from Non-immunogenic Haptens

Abstract: Functionalized nanomaterials have applications yet to be discovered, especially in the biological field and, in particular, the in vivo production of antibodies. In this paper, we show that aluminum oxide nanoparticles that are covalently coupled to haptens (small molecular mass compounds) activate the immune system, eliciting antibodies (polyclonal and monoclonal) specific for the herbicide atrazine, the antibiotic sulfasalazine, and the vitamin biotin in mice and rabbits. The particles play the role of carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…On the other hand, NPs play the role of carrier and adjuvant, with the immune response being dependent on size and crystallinity [26]. Transport of the NPs through the ECM is more complicated due to its’ inherent mesh-like organization [27].…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…On the other hand, NPs play the role of carrier and adjuvant, with the immune response being dependent on size and crystallinity [26]. Transport of the NPs through the ECM is more complicated due to its’ inherent mesh-like organization [27].…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…Aluminium is a commonly used adjuvant in vaccines [88,[96][97][98]. This stimulated some studies into the conjugation of antigen to aluminium nanoparticles [97,98].…”
Section: Inorganic Particlesmentioning
confidence: 99%
“…Aluminium is a commonly used adjuvant in vaccines [88,[96][97][98]. This stimulated some studies into the conjugation of antigen to aluminium nanoparticles [97,98]. These studies showed that the aluminium particles are able to play the role of both carrier and adjuvant to stimulate the immune system, although it has also been shown that aluminium particles are capable of adsorbing antigen so tightly that antigen structure is altered, which reduces vaccine efficacy [98,99].…”
Section: Inorganic Particlesmentioning
confidence: 99%
“…Aluminum (Al) salt-based adjuvants (most commonly in the form of aluminum oxyhydroxide (AlOOH), aluminum hydroxide (Al(OH) 3 ) are used in human vaccines since 1930s and are commonly referred to as "alum" [4][5][6]. The presence of oxygencontaining groups on their surface [7][8][9] provides fast antigen adsorption and yield a vigorous response from the immune system compared to alternatives [10]. While aluminum oxide (Al 2 O 3 ) is more robust, it is significantly less effective than other Al-based adjuvants and is commonly much less used.…”
Section: Introductionmentioning
confidence: 99%